Assessment of Regional Tourism Potential and the Role of Andijan Region - Farmonkul Tursunkulovich , Egamberdiev; Muhammadismoil Mukhitdinovich, Makhmudov (International Journal of Psychosocial Rehabilitation, 2020)
The rich history and nature of Uzbekistan show that the tourism industry has a high potential. We conducted research on modeling to assess the shortcomings and priorities of the tourism sector, which is one of the priorities of economic development of Uzbekistan.